Ecological Jihad in the Semantic Study of the Qur'an: An Analysis of the Meaning and Action of Environmental Conservation - Aqidahtul Jannah; Baso Pallawagau (Tilawah: Journal of Al-Qur'an Studies, 2025)
The issue of global environmental degradation requires a multi-perspective approach, including from a religious perspective. This article examines the concept of ecological jihad from the semantic perspective of the Qur'an as a form of spiritual and social responsibility of Muslims towards environmental preservation. This research aims to explore the meaning of the word jihad and related terms such as khalifah, fase, islah, and mizan to understand their semantic expansion in the contemporary ecological context. This study uses a qualitative approach with semantic-linguistic analysis of relevant Qur'anic verses. The results of the study indicate that jihad in the Qur'an is not limited to armed struggle, but encompasses various forms of earnest effort, including preserving the environment as a form of ecological jihad. These basic principles serve as an ethical and theological basis for building ecological awareness. Furthermore, ecological jihad is understood as a collective effort of the ummah to prevent damage to the earth (fasad fi al-ardh) through concrete actions ranging from a lifestyle revolution (reducing consumption, implementing zero-waste), participation in conservation (reforestation, waste management), environmental education, to advocacy for pro-environmental policies. Thus, ecological jihad can be interpreted as a form of devotion to God that reflects faith, social concern, and human responsibility as caliphs for stewardship of the earth. These actions are concrete manifestations of efforts to prevent damage to the earth and achieve the common good, in line with the spirit of jihad in the Quran as a constructive and beneficial struggle.life, humans must never escape from mistakes, especially Muslims. The Qur'an should be the main foundation in all walks of life and be a guide in every matter and problem, including in achieving repentance to Allah SWT. However, there are many factors that can mislead humans, lead to the wrong path and tempt humans to follow temptations, lusts that can lead to sin, especially in a life that is increasingly deviating from Islamic teachings. The result can destroy man and prevent him from doing good. Therefore, it is necessary for humans to refer to the Qur'an as a helper to get an understanding of asking for forgiveness for the sins that have been committed through repentance.